Sistem Pendukung Keputusan Pemberian Reward Karyawan Berdasarkan Kinerja Menggunakan Metode SAW - Terisia, Vany; Arman, Shevti Arbekti; Diana Yusuf; Fahrul Razi (ITB Ahmad Dahlan Jakarta, 2025)
Rewarding employees is one of the important strategies for improving motivation and performance within an organization. However, many companies face difficulties in determining which employees deserve rewards in a fair and objective manner. This research aims to develop a Decision Support System (DSS) that can assist in determining which employees are entitled to receive rewards based on several relevant criteria, using the Simple Additive Weighting (SAW) method. The SAW method is chosen for its ability to solve decision-making problems that involve multiple criteria with multi-attribute characteristics. The criteria used in this study include performance, discipline, contribution to the team, and initiative. The results of the study indicate that the application of the SAW method can produce objective and transparent decisions, as well as provide a solid basis for rewarding employees. The employee alternative with the highest score based on the SAW calculation is selected as the reward recipient, which is expected to enhance employee motivation and performance within the company. This research is expected to contribute to the development of a more systematic and data-driven reward system.